PERLINDUNGAN HUKUM ATAS TANAH ADAT DALAM KAITAN PEMBERIAN IZIN USAHA PERKEBUNAN KELAPA SAWIT - Septian Dirga Prayogo; Fitika Andraini (Jurnal Ilmiah Dinamika Hukum, 2023)
Rule point 3 of the UUPA states that the use and exploitation of agrarian lands, especially the management of ulayat land, is carried out by customary leaders (Kepala Adat) and the utilization is intended for both members of the customary law community concerned and people who are not part of the customary or local law community. Every citizen has the right to obtain legal remedies as well as remedies for violations of rights they have suffered as well as a fair legal settlement. In this case, the state has an obligation to ensure the fulfillment of these rights. Based on access to justice which is a constitutional guarantee of human rights. Likewise in the explanation of Law no. 39 of 1999 concerning Human Rights Article 6 Paragraph (1) states that customary rights which are actually still valid and upheld within the customary law community must be respected and protected in the context of protecting and enforcing human rights in the community concerned by taking into account the law and regulations. laws and regulations. The approach method used in the preparation of this thesis is normative juridical research (normative legal research method). The normative juridical research method is a legal research library conducted by examining library materials or secondary data. By using the deductive method of thinking (a way of thinking in drawing conclusions from something general that has been proven true and that conclusion is aimed at something specific). Based on the analysis that the author conducted regarding the Recognition of Ulayat Rights in the Republic of Indonesia, the district/city government is the first line to provide recognition and protection of customary rights over customary law community lands. Regional autonomy, which forms local governments that are close to the people, is expected to increase legal recognition and protection of the customary rights of customary law communities which are often neglected in state life. Key Word: Oil Palm, Law Protection, Customary Land.